Effectiveness of a comprehensive yoga program on convicted extremist offenders - Kanchibhotla, Divya; Kulkarni, Shashank; Singh, Shweta (International journal of yoga, 2020)
Objective: The present study aimed to explore the effect of yoga techniques on well-being and behavior among those who have propagated and participated in extreme violence and aggression. The sample comprised 219 United Liberation Front of Assam militants selected immediately after surrender of arms in the year 2012 from all over northeast region of India. Methodology: The study design was a single group with pre- and posttest assessment. All participants attended a 40-day intensive Yoga workshop (Sudarshan Kriya Yoga, Pranayama, Physical postures or Hatha Yoga, Meditation) conducted at Art of Living International Centre, Bengaluru. The impact of spiritual practices was observed on peace, aggression, life satisfaction, and quality of life in individuals using the aggression Buss Perry questionnaire, WHOQOL-BREF, and Satisfaction with Life Scale. The questionnaires were administered at the beginning and at the end of the 40-day workshop. Results: Significant results using paired t-test clearly demonstrate that by following yoga techniques (Sudarshan Kriya, Yoga, and Meditation), a reduction in aggression, quality of life, and life satisfaction can be obtained. These practices can be useful for people who want to rehabilitate themselves after incarceration or experience of militancy. The purpose of these measures is to reduce the risk of future criminality by those already convicted of violent extremist offenses, thereby protecting public safety while also benefiting individuals and communities.